Analisis Manajemen Kepala Sekolah dalam Meningkatkan Kompetensi Guru pada Lembaga Pendidikan - Yulianto, Tri; Siswanto, Nopri Dwi; Indra, Hasbi; Al-Kattani, Abdul Hayyie (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
As a top manager, of course the role of the school principal in managing and improving teacher competence cannot be ignored. The principal has a very significant role in creating a learning environment and can support, motivate and encourage teachers to continue to develop their abilities. Starting from preparing relevant professional programs to applying technology to innovative education. In carrying out their role, school principals must also be able to overcome obstacles or problems such as (SD) limited resources, resistance to change, and dynamics that are said to be complex in educational institutions. Collaboration with teachers, parents and the surrounding community is an important key in creating a holistic and sustainable educational ecosystem. This type of research is qualitative with a library research approach. The collection of literature related to the above theme can be classified into two. Firstly, primary sources (primary sources) and secondly secondary sources (secondary sources).